Infl uence of selenium deficiency on neural tube defects - Vats, Rajeev (Asian Journal of Medical Sciences, 2014)
Objective: As for the role of selenium on human fetal development, a little data is available in literature. The purpose of this manuscript was to study the influence of selenium on neural tube defects. This study will be helpful in planning strategies for prevention of neural tube defects. Methodology: After collection of the venous blood the same was immediately centrifuged and after immediate centrifugation, the clear serum was transferred to deionized plastic vials, stored and frozen at –20º C until determination of the analysis was carried out. The selenium levels as ng/ml were determined on GBC 932 spectrophotometer by fluorometery. Results: The mean maternal blood serum and cell mass concentrations in NTD group (306.4 ± 10.95 ng/ml, 192.44 ± 6.12 ng/ml, 165.8 ± 16.99 ng/g respectively) were significantly lower than those of control mothers (363.75 ± 17.1 ng/ml, 242.34 ± 15.7 ng/ml, 260.0 ± 20.57 respectively). A significant decrease in concentration of selenium in newborns with NTD (298.4 ± 12.3 ng/ml, 96.3 ± 7.15 ng/ml, 139.8 ± 27.5 ng/g respectively) as compared with healthy babies (358.1 ± 16.11 ng/ml, 122.44 ± 6.03 ng/ml, 268.6 ± 31.37 ng/g respectively). Conclusion: Selenium deficiency in mothers during pregnancy thought to be one of the factors responsible for NTDs. However, the lowered selenium concentrations in blood, serum and cell mass can be secondary cause of an abnormal pregnancy and didn’t contribute to its production. More investigations on selenium status in mothers during antenatal period, especially in prenatal development and antenatal selenium status including normal babies and NTD babies are required. DOI: http://dx.doi.org/10.3126/ajms.v6i2.11151 Asian Journal of Medical Sciences Vol.6(2) 2015 62-65